The non-contractual liability in Colombia of de facto administration - Angulo Marquinez, Diana Maryury (DIXI, 2020)
Subject and scope: The objective of this article is to establish the extra-contractual liability attributable to the Administration as a consequence of judicial police functions.Characteristics: The proposed investigation is important because it is an analysis of factual circumstances of common occurrence in the Colombian case (i) due to the high level of conflict in Colombia by the concentration of judicial police functions in the Cuerpo Técnico de Investigación (cti) of the Fiscalía General de la Nación, the high number of officials and employees linked to this essential body in the structure of the judicial body in charge of investigating punishable acts; and (ii) due to the significant incursion of personnel linked to conduct, contrary to the legal order, in the exercising of their assigned functions.Findings: Obligations form the legal basis for the theory of liability in the civil field; and legal acts and facts are the source of obligations. From the illegal act, legal responsibility finds its legal basis in that it forces the person who has caused a loss to repair the damage committed.Conclusions: The transition from the Absolute State to the State of Law and later to the Social State of Law brought, among other consequences, the transformation of the unaccountable State to the State that is financially responsible for the damages caused by its agents.
Keywords: concentration of functions; social rule of law; legal order; tort liability; de facto routes